ABC transporters are predictors of treatment failure in acute myeloid leukaemia - Cerovska, Ela; Salek, Cyril; Kundrat, David; Sestakova, Sarka; Pesek, Adam; Brozinova, Ivana; Belickova, Monika; Remesova, Hana (Biomedicine & pharmacotherapy, 2024)
INTRODUCTION: To date, no chemoresistance predictors are included in acute myeloid leukaemia (AML) prognostic scoring systems to distinguish responding and refractory AML patients prior to chemotherapy. ABC transporters have been described as altering AML chemosensitivity; however, a relevant study investigating their role at various molecular levels was lacking. METHODS: Gene expression, genetic variants, methylation and activity of ABCA2, ABCA5, ABCB1, ABCB6, ABCC1, ABCC3 and ABCG2 were analysed in AML blasts and healthy myeloblasts. Differences between responding and refractory AML in a cohort of 113 patients treated with 3 + 7 induction therapy were explored. RESULTS: ABCC3 variant rs2301837 (p = 0.049), ABCG2 variant rs11736552 (p = 0.044), higher ABCA2 (p = 0.021), ABCC1 (p = 0.017), and ABCG2 expression (p = 0.023) and a higher number of concurrently overexpressed transporters (p = 0.002) were predictive of treatment failure by multivariate analysis. Expression of ABCA5 (p = 0.003), ABCB6 (p = 0.001) and ABCC3 (p < 0.0001) increased significantly after chemotherapy. Higher ABCG2 promoter methylation correlated with lower ABCG2 expression (p = 0.0001). ABCC1 was identified as the most active transporter in AML blasts by functional analysis. CONCLUSIONS: ABC transporters, especially ABCC1 seem to contribute substantially to AML chemoresistance. A detailed understanding of chemoresistance mechanisms and the clinical implications of chemosensitivity predictors may lead to alternative therapeutic approaches for AML patients with unveiled chemoresistance signatures.
Keywords: ABC transporter; chemorezistence; ABC transportéry; Treatment Failure; Humans; Leukemia, Myeloid, Acute; Drug Resistance, Neoplasm; Anthracycline; ATP-Binding Cassette Transporters; Chemoresistance; Acute myeloid leukemia; lidé; neúspěšná terapie; akutní myeloidní leukemie